TANGGAPAN TERHADAP RUWATAN CARA KATOLIK - H. Pidyarto (Studia Philosophica et Theologica, 2006)
There is a widespread belief among Indonesian people (especially among the Javenese) that certain people (e.g. only child; a son who has only one brother but no sister) find themselves in a given situation, called sukerto, namely a situation which automatically brings to those people misery, misfortune or at least unpleasant situations. They are destined to be victims of an evil power, the socalled Bathara Kala. In order for them to be freed from this sukerto they should undergo a religious ritual called ruwatan (from the Javenese word ruwat, meaning to free, to release). This ritual consists of, among other things, a performance of Wayang Kulit (shadow puppet) with a special story. Some Roman Catholics (priests as well as lay people) perform ruwatan. They do this for the sake of inculturation of the Gospel, i.e. the process of integrating Gospel’s values into local cultures. They link the idea of ruwatan with some biblical verses; they also compare it with the notion of sin and of indulgence. This short article aims at showing that it is difficult, if not impossible, to adopt ruwatan and adapt it into Christianity.